Influencia de la educación ambiental en la promoción de la sostenibilidad y mitigación al cambio climático en la parroquia de Tanicuchi, cantón Latacunga, provincia de Cotopaxi 2023 - Vinocunga Viracucha, Pamela Liseth (2024)
The research focuses on the generation of environmental sustainability indicators with the aim of strengthening environmental education in the parish of Tanicuchi, located in the canton of Latacunga, belonging to the province of Cotopaxi. The methodology implemented is guided by a mixed approach, based on a literature review that facilitated the identification of environmental problems. To address these problems, a qualitative analysis was carried out through the Atlas.Ti software, together with on-site visits and the conduct of 4 interviews with the administrative staff of the parish GAD of Tanicuchi, in addition to 373 surveys of the inhabitants. This approach ensured that detailed and accurate information on the current situation was obtained. These data served as the basis for the development of 60 indicators of environmental sustainability, evenly distributed in various key factors, addressing comprehensively different aspects crucial to the sustainable development of the parish. The indicators by factor are: 4 indicators for the education factor, 4 indicators for the waste management factor, 6 indicators for the community participation factor, 7 indicators for the conservation factor of green areas, 4 indicators for the economic aspects factor, 6 indicators for the greenhouse gas factor, 5 indicators for the water factor, 6 indicators for the soil factor, 6 indicators for the agriculture factor, 6 indicators for the tourism factor and 6 indicators for the energy factor. The purpose of using these indicators of sustainable development is to effectively address the identified environmental problems, such as poor knowledge about environmental education in the parish. This goal is achieved through the research mentioned above. The analysis of these indicators not only provides a detailed overview of the current situation, but also facilitates the formulation of alternatives in order to improve the sustainability and sustainability of the parish. Ultimately, this initiative contributes to a more equitable and environmentally friendly development.